FENOMENA S-LINE DI MEDIA SOSIAL : TINJAUAN ETIKA DAN MORALITAS DALAM PERSPEKTIF HADIS - Rismalia Nurhaliza; Uswatun Hasanah; Sulaiman Mohammad Nur (Farabi, 2026)
The S-Line phenomenon on social media represents a digital cultural trend that originates from the Korean drama S-Line and has brought about ethical concerns in the realm of public digital spaces. The symbol of the “red line,” which initially signified intimate relationships, has evolved into an expression of self-identity, resulting in questions regarding privacy, modesty, and the disclosure of personal matters. This research seeks to examine the S-Line trend and its ethical ramifications through the lens of hadith. Employing a qualitative methodology that involves virtual field research, data were obtained by observing social media content and user interactions. The results indicate that S-Line serves not only as a source of entertainment but also as a medium for individuals to represent their identities by publicly displaying personal elements, either with full awareness or simply by conforming to popular trends. Viewed from the perspective of hadith, this phenomenon is associated with the prohibition against al-mujāharah and underscores the importance of ḥayā’ (modesty) in safeguarding personal dignity. Consequently, the S-Line phenomenon exemplifies a transformation in moral standards within the digital era, highlighting the need for ethical guidance grounded in prophetic teachings.